(3GdGSJKeGQ aj GdJQNjU GdGeJjGRj (B((3GdaQGfTGjR(B) /s - (3MHjH, eUWai SdeGfs ((3YeGf(B: s (3OGQ GdKbGaI ddfTQ(B, s, 2008)
(3GdUabGJ GdGeJjGRjI (B-(3CfhGY GdQNU GdGeJjGRjI (B-(3MSfGJ heSGhF GdJQNjU GdGeJjGRj (B-(3HfhO GJaGbjI GdJQNjU GdGeJjGRj (B-(3GdGYJHGQGJ GdbGfhfjI dCTcGd GdJQNjU (B-(3GdYeGd hGdehXahf aj GdhMOI GdGeJjGRjI (B-(3GdGSJTGQGJ GdegfjI hGdJbGYO (B-(3Jehjd GdJQNjU GdGeJjGRj (B-(3Jbjje GdJQNjU GdGeJjGRjs
(3HjHdjhZQGajG U(B.192 s
Keywords: (3GdGSJKeGQs; (3GdJQGNjUs